Earliest rock fabric formed in the Solar System preserved in a chondrule rim - Bland, Phil; Howard, L.; Prior, D.; Wheeler, J.; Hough, R.; Dyl, Kathryn (Nature Publishing Group, Macmillan Publishers Ltd, 2011)
Rock fabrics – the preferred orientation of grains – provide a window into the history of rock formation, deformation and compaction. Chondritic meteorites are among the oldest materials in the Solar System1 and their fabrics should record a range of processes occurring in the nebula and in asteroids, but due to abundant fine-grained material these samples have largely resisted traditional in situ fabric analysis. Here we use high resolution electron backscatter diffraction to map the orientation of sub-micrometre grains in the Allende CV carbonaceous chondrite: the matrix material that is interstitial to the mm-sized spherical chondrules that give chondrites their name, and fine-grained rims which surround those chondrules. Although Allende matrix exhibits a bulk uniaxial fabric relating to a significant compressive event in the parent asteroid, we find that fine-grained rims preserve a spherically symmetric fabric centred on the chondrule. We define a method that quantitatively relates fabric intensity to net compression, and reconstruct an initial porosity for the rims of 70-80% - a value very close to model estimates for the earliest uncompacted aggregates2,3. We conclude that the chondrule rim textures formed in a nebula setting and may therefore be the first rock fabric to have formed in the Solar System.